Systematic Construction and Validation of a Prognostic Model for Hepatocellular Carcinoma Based on Immune-Related Genes - Yu, Jiahao; Ma, Shuoyi; Tian, Siyuan; Zhang, Miao; Ding, Xiaopeng; Liu, Yansheng; Yang, Fangfang; Hu, Yinan; Xuan, Guoyun; Zhou, Xinmin; Wang, Jingbo; Han, Ying (Frontiers in Cell and Developmental Biology, 2021)
Hepatocellular carcinoma (HCC), a highly aggressive tumor, has high incidence and mortality rates. Recently, immunotherapies have been shown to be a promising treatment in HCC. The results of either the CheckMate-040 or IMbrave 150 trials demonstrate the importance of immunotherapy in the systemic treatment of liver cancer. Thus, in this study, we tried to establish a reliable prognostic model for liver cancer based on immune-related genes and to provide a new insight for immunotherapy of HCC. In this study, we used four datasets that incorporated 851 HCC samples, including 340 samples with complete clinical information from TCGA database, to establish an effective model for predicting the prognosis of HCC patients based on the differential expression of immune-related genes (IRGs) and validated the prognostic model using the data from ICGC. The top 6 characteristic IRGs identified by protein-protein interaction (PPI) network analysis, MMP9, FOS, CAT, ESR1, ANGPTL3 and KLKB1, were selected for further study. In addition, we assessed the correlations of the 6 characteristic IRGs with the tumor immune microenvironment, clinical stage, and sensitivity to anticancer drugs. We also explored whether the differential expression of the characteristic IRGs was specific to HCC or present in most cancers. The expression levels of the 6 characteristic IRGs were significantly different between most tumor tissues and adjacent normal tissues. In addition, these characteristic IRGs showed a strong association with immune cell infiltration in HCC patients. We found that MMP9 and ESR1 were independent prognostic factors for HCC, while CAT, ESR1, and KLKB1 were associated with the clinical stage. We collected HCC paraffin sections from 24 patients from Xijing hospital to identify the differential expression of the 5 genes (MMP9, ESR1, CAT, FOS, KLKB1). Finally, the results of decision curve analysis and nomogram revealed that our models provided a prognostic benefit for most HCC patients and the predicted overall survival was consistent with the actual overall survival. In conclusion, we systemically constructed a novel prognostic model that provides new insights into HCC.